KARAKTERISTIK HUKUM ISLAM DALAM PERUBAHAN SOSIAL - Rozin, Musnad (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2016)
As the last celestial religions, Islam has the Mission of rahmatan lil'alamin, namely spreading of mercy for all of nature. The presence of Islam is not for a specific community or tribe, but for the whole of nature and its content. As a universal religion, Islam's payload was designed to cover a wide range of sectors and lines of human life of the Muslims. Islamic law derived aims to prevent damage to the community and bring benefits. In this case it is based on five key priorities i.e. keeping religion, soul, intellect, lineage and property. With based on the Qur'an that is universal and dynamic. Islamic law with all its benefits, is a rule which aims to provide good and ease to the human race. Thus, Islamic law had some characteristics that are not owned by the law anywhere in the world. These characteristics include its flexibility. The flexible nature of the existence, in addition to the convenience of the people in command of actualize, is also a form of concrete from the Humanities Law